Nucleated red blood cells as predictor of all-cause mortality in emergency department - Narci, Huseyin; Oktay, Mehmet Murat; Ayrık, Cüneyt; Çimen, Mehmet Burak Yavuz (W.B. Saunders, 2020)
Bacground: Nucleated red blood cells (NRBCs) are immature erythrocytes that are not normally detected in the blood of healthy adults. The detection of these cells in peripheral blood is associated with increased mortality and poor prognosis. In this study, we aimed to investigate whether NRBCs predict for all causes of death in patients admitted to the emergency department (ED). Method: This study was conducted retrospectively between January 2019 and December 2019 in academic emergency department, faculty of medicine. We included all patients who died of non-traumatic causes and The control group consisted of patients discharged from the ED. NRBCs and other laboratory parameters were compared between the two groups. The primary outcome is all-cause mortality in the ED. Multivariate logistic analysis was performed. Results: A total of 204 patients (119 male) were included in the study. The mean age of the patients was 66.7 ± 14.6 years. NRBC value was higher in those who died (678.43 ± 655.16/ μl) compared to the control group (22.55 ± 57.86/ μl) (P < 0.001). According to receiver operating characteristic curve analysis (ROC) performed for the prediction all cause mortality in the ED, the best cut-off point for NRBC was >0 /μl (sensitivity 94,12%, specificity 82,35%, Area Under Curve (AUC) =0.97). In the multivariate logistic regression analysis, the NRBC was associated with all-cause mortality in the ED (odds ratio,OR = 1.020, confidence interval, CI = 1.012–1.028). Conclusıons: High blood levels of nucleated red blood cells at admission to the emergency department may be associated with increased mortality. © 2020 Elsevier Inc.
Keywords: Emergency department; Mortality; Nucleated red blood cells